2008
DOI: 10.1111/j.1745-493x.2008.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

The Information Technology Capability of Third‐party Logistics Providers: A Resource‐based View and Empirical Evidence From China

Abstract: Third‐party logistics (3PL) providers have become important players in global supply chain management as increasing numbers of firms are outsourcing their logistics activities. However, the role of the information technology (IT) capability of these 3PL providers has not drawn much research attention. The way in which 3PL providers develop IT capability and how IT capability affects their competitive advantage deserve further investigation. This study has developed and tested a research model to address these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
148
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(159 citation statements)
references
References 63 publications
5
148
1
5
Order By: Relevance
“…One exception is a recent paper by Lin and Ho (2009), where the authors find a positive correlation between the willingness to adopt RFID technologies and supply chain performance. Previous survey-based studies focused on 3PLs' capabilities and performance (Lai et al, 2006;Lai et al, 2008) do not allow a direct comparison with this research since their IT variables have been measured in a much more generic way (e.g.…”
Section: It Adoption and Firm Performancementioning
confidence: 99%
See 3 more Smart Citations
“…One exception is a recent paper by Lin and Ho (2009), where the authors find a positive correlation between the willingness to adopt RFID technologies and supply chain performance. Previous survey-based studies focused on 3PLs' capabilities and performance (Lai et al, 2006;Lai et al, 2008) do not allow a direct comparison with this research since their IT variables have been measured in a much more generic way (e.g.…”
Section: It Adoption and Firm Performancementioning
confidence: 99%
“…Evangelista and Sweeney (2006) also identify information technologies as an enabler for developing logistics capabilities that 3PLs can directly offer to the market via the provision of value added services. Moreover, Lai et al (2006) and Lai et al (2008) found a positive correlation between the IT capability of 3PLs and the provision of innovative and customised services.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome this issue, many studies have shown that the implementation of IT is significantly positively associated with firm performance; both in terms of logistics efficiency and effectiveness in delivering the services (Evangelista et al, 2012;F. Lai, Li, Wang, & Zhao, 2008;Langley et al, 2007;Qiang Wang & Zhao, 2008).…”
Section: Introductionmentioning
confidence: 99%